Improving the quality of care for preterm infants in the golden hour - Nalina Amuji; Shashidhar Appaji Rao; Prashantha Yemmethimmanahalli Nagaraju; Kanekal Gautham Suresh; Sofia Steven; Chandrakala Bada Shekharappa (BMJ Open Quality)
Background The quality of care provided during the first golden hour after birth in preterm neonates significantly impacts both short- and long-term outcomes. However, implementation of these care processes varies across centres, is not standardised and affects the quality of care.Aim To improve the quality of care provided during the first golden hour in neonates born at <34 weeks’ gestation.Methods This quality improvement initiative was conducted in a 30-bedded tertiary care teaching hospital in southern India over 28 months (April 2019–July 2021). Evidence-based interventions to improve admission temperature, respiratory care and administering parenteral nutrition and antibiotics during the golden hour were implemented through Plan-Do-Study-Act cycles in four phases for eligible neonates. The effect of these practice changes on clinical outcomes, including intraventricular haemorrhage, necrotising enterocolitis, retinopathy of prematurity, bronchopulmonary dysplasia and survival ratewere studied.Results A total of 311 eligible neonates were included in the study. Admission hypothermia significantly reduced from 79% to 22% (p=0.003), and adherence to the respiratory bundle improved from 13% to 77% (p<0.001). The time taken for administration of parenteral nutrition improved from 102±23 min to 62.5±26.7 min (mean±SD) (p<0.001). The median time for administration of antibiotics improved from 162 (135, 173) min to 74 (69, 102) min (median±IQR) (p=0.001) and improvement in mean blood glucose from 35 (12) mg/dL to 54 (14) mg/dL (mean±SD) (p<0.001) at neonatal intensive care unit (NICU) admission, and admission time to NICU from 66.4±16 min to 41±13.8 min (p<0.001).Conclusion Quality improvement project of improving care in the golden hour after birth in < 34 weeks neonates reduces admission hypothermia and hypoglycaemia and improves the time of admission to NICU, and time of administration of parenteral nutrition and antibiotics.